'Forbidden' intersubband optical transitions in quantum well structures in a tilted magnetic field. (21st August 2018) - Telenkov, M P; Mityagin, Yu A; Doan, T N V; Nagaraja, K K
Abstract: In this paper, we report on the behavior of intersubband optical absorption and emission spectrum in quantum well structures with an asymmetrical potential profile in a quantizing magnetic field tilted with respect to the layers in the considered structure. The analysis of the effect of both the magnetic field value and orientation and potential profile of a quantum well structure on the intensity of the 'forbidden' ( Δ n ≠ 0 ) intersubband optical transitions is presented. We also present the approximate analytical expression for the estimation of the contribution to the absorption/emission coefficient of intersubband transitions with different Δ n .